Acetaminophen-induced liver injury is mediated by the ion channel TRPV4 - Echtermeyer, Frank; Eberhardt, Mirjam; Risser, Linus; Herzog, Christine; Gueler, Faikah; Khalil, Mohammad; Engel, Matthias; Vondran, Florian; Leffler, Andreas (The FASEB Journal, 2019)
Overdosing of the analgesic acetaminophen (APAP) is one of the most common causes for acute liver failure in modern countries. Although the exact molecular mechanisms mediating hepatocellular necrosis are still elusive, it is preceded by oxidative stress triggered by excessive levels of the metabolite N-acetyl-para-benzoquinone imine (NAPQI). Here, we describe the role of the redox-sensitive transient receptor potential (TRP) ion channel TRP vanilloid 4 (TRPV4) for APAP-induced hepatoxicity. Both pharmacological inhibition and genetic deletion of TRPV4 ameliorate APAP-induced necrosis in mouse and human hepatocytes in vitro. Liver injury caused by a systemic overdose of APAP is reduced in TRPV4-deficient mice and in wild-type mice treated with a TRPV4 inhibitor. The reduction of hepatotoxicity accomplished by systemic TRPV4 inhibition is comparable to the protective effects of the antioxidant N-acetyl-cysteine. Although TRPV4 does not modulate intrahepatic levels of glutathione, both its inhibition and genetic deletion attenuate APAP-induced oxidative and nitrosative stress as well as mitochondrial membrane depolarization. NAPQI evokes a calcium influx by activating heterologously expressed TRPV4 channels and endogenous TRPV4 channels in hepatoma cells but not in primary mouse hepatocytes. Taken together, our data suggest that TRPV4 mediates APAP-induced hepatotoxicity and thus may be a suitable target for treatment of this critical side effect.-Echtermeyer, F., Eberhardt, M., Risser, L., Herzog, C., Gueler, F., Khalil, M., Engel, M., Vondran, F., Leffler, A. Acetaminophen-induced liver injury is mediated by the ion channel TRPV4.
CRIS-Team WoS Importer:2019-09-10